KEPEMIMPINAN KEPALA DESA DALAM MENINGKATKAN PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DI DESA TANJUNG MEKAR KECAMATAN SAMBAS KABUPATEN SAMBAS - Azhar, Azhar; Setiawan, Irfan (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2024)
Lack of persuasive relationship between the Village Head and the entire community in the village. This is what causes a lack of communication process between the village head and the community in planning and implementing village development. The leadership of the village head has a big role in determining the direction of policy in development in the village. This research aims to determine the leadership of the Tanjung Mekar Village Head in increasing community participation in village development. This research uses a descriptive method with a survey approach. The research sample included the Village Head, village officials and the community. Data was collected through interviews, questionnaires and observations. The research results show that the leadership of the Tanjung Mekar Village Head in increasing community participation in village development is classified as "Quite Good". The Village Head is assessed as having intelligence, emotional maturity, high motivation, a drive for achievement, and a good attitude towards human relations. However, there are several suggestions for increasing community participation, such as increasing communication, transparency and community involvement in development planning. Overall, this research provides insight into the importance of effective village head leadership in encouraging community participation and achieving village development goals.